Pandangan Masyarakat Kampung Menteng terhadap Penggunaan Alat Musik Hadrah di Masjid Raya An-Nuh: Studi Living Hadis - Firmansyah; Datmi, Muhammad Akbar Rosyidi (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study examines the community’s understanding of the use of musical instruments at An-Nuh Grand Mosque in Kampung Menteng from a hadith perspective. The aim of this research is to explore the theological, social, and cultural dynamics underlying differing views on this practice, as well as its implications for religious life. The study employs a qualitative descriptive-analytical and phenomenological approach. Data were collected through in-depth interviews with mosque administrators, religious leaders, and congregants, along with field observations and documentation of hadith texts and relevant academic literature. The findings reveal three main themes. First, theological diversity influenced by differing interpretations of hadith concerning music, ranging from strict prohibition to conditional permissibility. Second, the influence of local culture, which positions music as part of religious expression and community identity. Third, the role of authority and tradition in shaping mosque policies, which often function as a mediating space between conservative and progressive groups. These findings demonstrate that the use of music in the mosque is not merely a ritual issue, but also a reflection of negotiation between text, tradition, and contemporary social realities. This study contributes to hadith studies and Islamic cultural scholarship by showing that the living hadith approach can harmonize textual authority with lived religious practices. Its practical implication highlights the need for participatory and dialogical mosque governance to prevent internal conflict and strengthen congregational harmony. Further research is recommended to compare similar cases across different cultural contexts.